Yield performance and optimal nitrogen and phosphorus application rates in wheat and faba bean intercropping - Jing-xiu XIAO; Ying-an ZHU; Wen-lian BAI; Zhen-yang LIU; Li TANG; Yi ZHENG (Journal of Integrative Agriculture)
Yield performance in cereal and legume intercropping is related to nutrient management, however, the yield response of companion crops to nitrogen (N) input is inconclusive and only limited efforts have focused on rationed phosphorous (P) fertilization. In this study, two multi-year field experiments were implemented from 2014–2019 under identical conditions. Two factors in a randomized complete block design were adopted in both experiments. In field experiment 1, the two factors included three planting patterns (mono-cropped wheat (MW), mono-cropped faba bean (MF), and wheat and faba bean intercropping (W//F)) and four N application rates (N0, 0 kg N ha–1; N1, 90 and 45 kg N ha–1 for wheat and faba beans, respectively; N2, 180 and 90 kg N ha–1 for wheat and faba beans, respectively; and N3, 270 and 135 kg N ha–1 for wheat and faba beans, respectively). In field experiment 2, the two factors included three P application rates (P0, 0 kg P2O5 ha–1; P1, 45 kg P2O5 ha–1; and P2, 90 kg P2O5 ha–1) and the same three planting patterns (MW, MF, and W//F). The yield performances of inter- and mono-cropped wheat and faba beans under different N and P application rates were analyzed and the optimal N and P rates for intercropped wheat (IW) and MW were estimated. The results revealed that intercropping favored wheat yield and was adverse to faba bean yield. Wheat yield increased by 18–26%, but faba bean yield decreased by 5–21% in W//F compared to MW and MF, respectively. The stimulated IW yield drove the yield advantage in W//F with an average land equivalent ratio (LER) of 1.12. N and P fertilization benefited IW yield, but reduced intercropped faba bean (IF) yield. Nevertheless, the partial LER of wheat (pLERwheat) decreased with increasing N application rates, and the partial LER of faba bean (pLERfaba bean) decreased with increasing P application rates. Thus, LER decreased as N input increased and tended to decline as P rates increased. IW maintained a similar yield as MW, even under reduced 40–50% N fertilizer and 30–40% P fertilizer conditions. The estimated optimum N application rates for IW and MW were 150 and 168 kg ha–1, respectively, and 63 and 62 kg ha–1 for P2O5, respectively. In conclusion, W//F exhibited yield advantages due to stimulated IW yield, but the intercropping yield benefit decreased as N and P inputs increased. Thus, it was concluded that modulated N and P rates could maximize the economic and ecological functions of intercropping. Based on the results, rates of 150 kg Nha–1 and 60 kg P2O5 ha–1 are recommended for IW production in southwestern China and places with similar conditions.